2000
DOI: 10.1159/000055949
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Occipitocervical Arthrodesis

Abstract: Object: Few reports exist on the options and effectiveness of craniocervical stabilization in the pediatric population compared with the adult literature. Traditional options in children include onlay grafting and semi-rigid occipitocervical wiring. Recently, reports on the use of rigid internal fixation devices such as occipitocervical plates and contoured loops have provided excellent results in adults, and their use has often obviated the need for external orthosis. The purpose of this article is to report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The investigations required for the diagnosis and treatment of AAD are very well documented [3, 13, 14, 15, 16, 17, 18]. We now follow an algorithm which makes our study more informative and cost effective and does away with unnecessary investigations:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations required for the diagnosis and treatment of AAD are very well documented [3, 13, 14, 15, 16, 17, 18]. We now follow an algorithm which makes our study more informative and cost effective and does away with unnecessary investigations:…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been only 10 publications [15, 16, 17, 24, 25, 26, 27, 28, 29, 30], comprising about 130 children, that have focused specifically on the problem of surgical stabilization of the upper cervical spine and the CV junction in the pediatric and adolescent population. Also, ours is probably the first publication dealing exclusively with the management of children with congenital AAD and problems arising therefrom in children from a developing country.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Recent reports have demonstrated that instrumented internal occipitocervical fixation is a reasonable therapeutic option, even for pediatric patients. 1,2,4,5,11,17) Instrumented internal occipitocervical fixation augments the success rate of arthrodesis with minimal use of halo orthoses in pediatric patients. 4) Rigid internal fixation using screw techniques provides superior biomechanical stability and obviates the need for halo orthoses.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) However, concerns regarding subaxial spinal biomechanics in children undergoing occipitocervical fixation include acquired instability at caudal levels to the fusion site, abnormal spinal curvature, and growth disturbance of the fused vertebral levels. 17) These concerns are still controversial. 1,2,11) For example, occipitocervical fixation in children resulted in increased lordotic curvature of the cervical spine, but reports over the last decade have come to different conclusions with some studies suggesting that these changes are not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Usage of instrumentation in young children has been reported, but these were mainly instances of upper cervical spine instrumentation applied posteriorly [2, 16, 17]. A few cases of anterior cervical plate applications in children below the age of 8–10 years have appeared in the literature [3, 18].…”
Section: Discussionmentioning
confidence: 99%